2017
DOI: 10.1109/lsens.2017.2737956
|View full text |Cite
|
Sign up to set email alerts
|

Transparent Flexible Active Faraday Cage Enables In Vivo Capacitance Measurement in Assembled Microsensor

Abstract: Capacitive micro-sensors such as accelerometers, gyroscopes and pressure sensors are increasingly used in the modern electronic world. However, the in vivo use of capacitive sensing for measurement of pressure or other variables inside a human body suffers from significant errors due to stray capacitance. This paper proposes a solution consisting of a transparent thin flexible Faraday cage that surrounds the sensor. By supplying the active sensing voltage simultaneously to the deformable electrode of the capac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…6b ). The 20 nF/N sensitivity of the paper-based supercapacitive sensors is more than 1000 times higher than that of traditional MEMS capacitive sensors 50 , 51 . The range of measurement of the sensors depends on the design of the sensors.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…6b ). The 20 nF/N sensitivity of the paper-based supercapacitive sensors is more than 1000 times higher than that of traditional MEMS capacitive sensors 50 , 51 . The range of measurement of the sensors depends on the design of the sensors.…”
Section: Resultsmentioning
confidence: 89%
“…The sensitivity of our paper-based supercapacitive sensors depends on the size and configuration of the sensors, ranging from several nF/N to several μF/N. In contrast, typical sensitivities of traditional MEMS capacitive sensors are on the order of pF/N 50 , 51 . Figure 6a shows the capacitive response to applied forces for the supercapacitive sensor made of the corrugated electrolyte (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…50 Additionally, miniaturized Faraday cages have been fabricated to support such microscale sensors for use in complex matrices. 54 Furthermore, we have demonstrated that MIP-modified microelectrodes overcome the high solution resistance of natural surface water matrices and may use oxygen reduction as a redox mediator to generate a measurable signal without the addition of environmentally foreign redox mediators. This sensing platform holds promise for the generation of inexpensive, deployable electrochemical sensors capable of acting as a first line of defense against surface water contamination and potentially empowering citizen scientists to quantitatively discern the quality of their water.…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…Electrochemical analysis using microelectrodes is generally recognized to be an inexpensive sensing modality , based on the ease with which microelectrodes can be fabricated. , Perhaps the greatest cost consideration is the potentiostat used to make the measurement, a cost we have reduced by developing a $50 potentiostat amenable to microelectrode studies . Additionally, miniaturized Faraday cages have been fabricated to support such microscale sensors for use in complex matrices . Furthermore, we have demonstrated that MIP-modified microelectrodes overcome the high solution resistance of natural surface water matrices and may use oxygen reduction as a redox mediator to generate a measurable signal without the addition of environmentally foreign redox mediators.…”
Section: Resultsmentioning
confidence: 99%
“…pollute the sensor signal. The parasitic capacitance for in vivo use is of the order of femto or pico Farads according to previous research of our group ( [3,8,9]) and is hard to eliminate by estimation and subtraction.…”
mentioning
confidence: 99%